Investigating teachers' use of literacy-infused science strategies: A mixed methods study - Allison M. Esparza; Kenneth Fleming; Henan Zhang; Huiwen Pang; Cindy Guerrero; Rafael Lara-Alecio; Beverly J. Irby; Fuhui Tong (Springer, 2023)
Abstract The 2019 science results from the National Assessment of Educational Progress showed that 8th-grade students, especially economically challenged and emergent bilingual students, made few gains in science and reading achievement. Researchers have found that scientific language may be a significant barrier to student comprehension. Researchers have advocated for integrating effective literacy strategies into the science curriculum to assist students in science and reading outcomes. We investigated the enactment of literacy-infused science strategies of a group of participating seventh-grade science teachers in a federally funded project following monthly virtual professional development sessions. Results indicated that teachers self-reported an overall increase in their use of literacy-infused science strategies after participating in monthly literacy-infused virtual professional development.